Impact of Vitamin C and Hydroxyurea on the Reproductive System Health in Male Rats - Ebtesam Abdulhadi; Ghaliyah Aqeelah; Faiza Milad (AlQalam Journal of Medical and Applied Sciences, 2024)
Hydroxyurea (HU) is a medication used to treat various diseases and is also being studied for its effects on spermatogenesis. Vitamin C (VC), an antioxidant, has been shown to protect sperm cells from oxidative stress, potentially improving fertility and sperm quality. In a study involving twenty-four adult male albino rats divided into four groups, Group 1 served as the control, Group 2 received 5 mg of vitamin C, Group 3 received 100 mg of hydroxyurea per body weight, and Group 4 received a combination of vitamin C and hydroxyurea to assess essential functions of the reproductive system, including hormone levels, antioxidant markers, oxidative stress indicators, histopathology, and identification of DNA damage. The study found that hydroxyurea significantly reduced testicular weight, SOD, CAT, and GSH while increasing FSH and MDA levels and causing abnormalities in sperm morphology. Hydroxyurea also caused apparent alterations in the histological structure of the testes and comet parameters. Rats treated with vitamin C showed a significant increase in absolute and relative epididymis weight compared to the control group. Moreover, vitamin C intervention reversed the adverse effects observed in rats fed hydroxyurea, indicating that low doses of vitamin C can protect against testicular damage. الهيدروكسي يوريا هو دواء يستخدم لعلاج أمراض مختلفة ويتم دراسته أيضًا لتأثيراته على تكوين الحيوانات المنوية. وثبت أن فيتامين سي، أحد مضادات الأكسدة يحمي خلايا الحيوانات المنوية من الإجهاد التأكسدي، مما قد يؤدي إلى تحسين الخصوبة وجودة الحيوانات المنوية. في دراستنا شملت أربعة وعشرين من ذكور الفئران البيضاء البالغة مقسمة إلى أربع مجموعات، كانت المجموعة الأولى بمثابة المجموعة الضابطة، وتلقت المجموعة الثانية 5 ملغ من فيتامين سي، وتلقت المجموعة الثالثة 100 ملغ من هيدروكسي يوريا، بينما تلقت المجموعة الرابعة مزيجًا من فيتامين سي وهيدروكسي يوريا لتقييم الوظائف الأساسية للجهاز التناسلي، بما في ذلك مستويات الهرمونات، وعلامات مضادات الأكسدة، ومؤشرات الإجهاد التأكسدي، والتشريح النسيجي المرضي، وتحديد تلف الحمض النووي. وأظهرت الدراسة أن هيدروكسي يوريا سبب في انخفاض بشكل كبير في وزن الخصية، مع زيادة في مستويات SOD) ، CAT، GSH،FSH ، (MDA وتسبب في تشوهات في شكل الحيوانات المنوية. أيضًا تسبب الهيدروكسي يوريا في حدوث تغيرات واضحة في التركيب النسيجي للخصيتين والحمض النووي DNA بينما أظهرت الفئران المعالجة بفيتامين سي زيادة معنوية في وزن البربخ المطلق والنسبي مقارنة بالمجموعة الضابطة. علاوة على ذلك، أدى تدخل فيتامين سي إلى عكس الآثار الضارة التي لوحظت في الفئران التي تغذت على هيدروكسي يوريا، مما يشير إلى أن الجرعات المنخفضة من فيتامين سي يمكن أن تحمي من تلف الخصية